Constraints of paddy production among smallholding farmers / Zubaidah Yusop ... [et al.] - Yusop, Zubaidah; Abd Aziz, Ahmad Shahir; Saili, Abdul Rahman; Che Md Nor, Rumaizah; Sahmat, Siti Sahmsiah (Universiti Teknologi MARA Cawangan Sarawak, 2021)
The study was conducted in Samarahan Division, Sarawak to identify the production constraints faced by smallholding paddy farmers. This survey was conducted in four districts in Samarahan Division. All the respondents were selected randomly from the list of the registered paddy farmers obtained from Department of Agriculture Sarawak. There were 273 respondents from four districts participating in this study. Data were collected by using questionnaire survey. The obtained data were analysed by using correlation analysis and Multiple Linear Regressions (MLR) analysis. The finding reported that only physical and technology could be concluded as significant production constraint to the paddy production. Various suggestions of management practices also have been discussed to overcome the constraints towards a more sustainable paddy production.